A multiscale methodology quantifying the sintering temperature‐dependent mechanical properties of oxide matrix composites. Issue 7 (9th February 2018) - Jiang, Ru; Yang, Lingwei; Liu, Haitao; Tan, Wei; Sun, Xun; Cheng, Haifeng; Mao, Weiguo
Abstract: A novel methodology combining multiscale mechanical testing and finite element modeling is proposed to quantify the sintering temperature‐dependent mechanical properties of oxide matrix composites, like aluminosilicate (AS) fiber reinforced Al2 O3 matrix (ASf /Al2 O3 ) composite in this work. The results showed a high‐temperature sensitivity in the modulus/strength of AS fiber and Al2 O3 matrix due to their phase transitions at 1200°C, as revealed by instrumented nanoindentation technique. The interfacial strength, as measured by a novel fiber push‐in technique, was also temperature‐dependent. Specially at 1200°C, an interfacial phase reaction was observed, which bonded the interface tightly, as a result, the interfacial shear strength was up to ≈450 MPa. Employing the measured micro‐mechanical parameters of the composite constituents enabled the prediction of deformation mechanism of the composite in microscale, which suggested a dominant role of interface on the ductile/brittle behavior of the composite in tension and shear. Accordingly, the ASf /Al2 O3 composite exhibited a ductile‐to‐brittle transition as the sintering temperature increased from 800 to 1200°C, due to the prohibition of interfacial debonding at higher temperatures, in good agreement with numerical predictions. The proposed multiscale methodology provides a powerful tool to study the mechanical properties of oxide matrix composites qualitatively and quantitatively.